2015
DOI: 10.1021/es505084j
|View full text |Cite
|
Sign up to set email alerts
|

Air–Seawater Exchange of Organochlorine Pesticides along the Sediment Plume of a Large Contaminated River

Abstract: Gaseous exchange fluxes of organochlorine pesticides (OCPs) across the air−water interface of the coastal East China Sea were determined in order to assess whether the contaminated plume of the Yangtze River could be an important regional source of OCPs to the atmosphere. Hexachlorocyclohexanes (HCHs), chlordane compounds (CHLs), and dichlorodiphenyltrichloroethanes (DDTs) were the most frequently detected OCPs in air and water. Air−water exchange was mainly characterized by net volatilization for all measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 66 publications
7
13
0
Order By: Relevance
“…At the sediment-water interface, the greatest PAH release from sediment was determined at locations within the PHSS and MCBSS, with high individual PAH and location variability reflecting the heterogeneity of the sediment. Hydrophobic contaminants in the sediment have the ability to be a source to the overlying water and ultimately to the air, as shown by Larsson [32] and more recently proposed to be the case in the sediment plume of the Yangtze River in China [44]. Examination of individual PAH flux patterns in the present study showed several cases supporting the possibility of sediments being a source to the air.…”
Section: Sediments a Source Of Vapor Phase Pahssupporting
confidence: 77%
“…At the sediment-water interface, the greatest PAH release from sediment was determined at locations within the PHSS and MCBSS, with high individual PAH and location variability reflecting the heterogeneity of the sediment. Hydrophobic contaminants in the sediment have the ability to be a source to the overlying water and ultimately to the air, as shown by Larsson [32] and more recently proposed to be the case in the sediment plume of the Yangtze River in China [44]. Examination of individual PAH flux patterns in the present study showed several cases supporting the possibility of sediments being a source to the air.…”
Section: Sediments a Source Of Vapor Phase Pahssupporting
confidence: 77%
“…However, the relative roles of the two sources remain poorly understood. The most recent study indicated that the major source of HCH and DDT was volatilization from seawater and the large contaminated Yangtze River served as a continuous significant regional secondary source to the upper atmosphere [ Lin et al , ]; however, that study focused only on one season (summer) rather than all four seasons, and only the air‐sea gas exchange flux was estimated. Therefore, further studies are necessary to more fully elucidate the seasonal source‐sink relationship according to fluxes of HCH and DDT in the region for the whole year.…”
Section: Introductionsupporting
confidence: 85%
“…DDT residues in agricultural soil were transported by enhanced riverine runoff to sustain net volatilization in summer. Lin et al [] concluded that the river plume including the Yangtze and Qiantang Rivers was unable to sustain the volatilization flux of DDT over a full year based on samples that had been collected only in summer. They assumed that DDT can show a deposition trend at other times to maintain the annual balance between riverine input and volatilization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations